1978
DOI: 10.1093/oxfordjournals.jbchem.a132099
|View full text |Cite
|
Sign up to set email alerts
|

Saturation Transfer Electron Spin Resonance Study on the Rotational Diffusion of Calcium- and Magnesium-Dependent Adenosine Triphosphatase in Sarcoplasmic Reticulum Membranes1

Abstract: The technique of saturation transfer electron spin resonance has been applied to study the rotational diffusion of spin-labeled Ca2+, Mg2+-dependent ATPase molecules in the membranes of sarcoplasmic reticulum vesicles. Comparison of the present data with those for spin-labeled hemoglobin undergoing isotropic rotation leads to a value of 2 X 10(-4) s for the apparent rotational correlation time at 20 degrees C for the membrane-bound protein. Consideration of the anisotropy of the Brownian rotation of the membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
1

Year Published

1979
1979
2005
2005

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 0 publications
1
22
1
Order By: Relevance
“…4) corresponds well with recent findings, by saturation transfer electron paramagnetic resonance techniques, of a discontinuity at this temperature when the data were plotted in an Arrhenius plot (7,8). Interestingly, the temperature at which the break for rotational motion is occurring also coincides with a discontinuity observed in the Arrhenius plot for enzymatic activity (see Fig.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…4) corresponds well with recent findings, by saturation transfer electron paramagnetic resonance techniques, of a discontinuity at this temperature when the data were plotted in an Arrhenius plot (7,8). Interestingly, the temperature at which the break for rotational motion is occurring also coincides with a discontinuity observed in the Arrhenius plot for enzymatic activity (see Fig.…”
supporting
confidence: 90%
“…Until recently, however, only a few measurements had been made of protein rotation in biomembranes by using laser flash-induced photodichroism (4)(5)(6). Recently there has been an increase in protein rotation studies and other techniques such as saturation electron paramagnetic resonance spectroscopy (7,8) have also been developed for this purpose. The relationship among the function of an enzyme, its rotational motion, and the fluidity of its lipid matrix is clearly of importance for our understanding at the molecular level of membrane enzymes and particularly for transport enzymes.…”
mentioning
confidence: 99%
“…Previously, two studies of the rotation of the Ca2+-ATPase in SR using saturation transfer EPR have been reported. Thomas & Hidalgo (1 978) found that the correlation time T~ varies from 60 to 20 ps over the range 4-20 OC, while Kirino et al (1978) obtained values of 800-200 ps over the same temperature range. Both groups agree that there is a change in temperature dependence at about 15-20 OC, with T~ becoming relatively temperature insensitive in the region of 20-37 OC.…”
Section: Discussionmentioning
confidence: 97%
“…The transition in the temperature dependence of enzyme activity is associated with a change in the rotational motion of the ATPase protein, suggesting either a change in protein conformation or a change in proteinprotein interaction around 15°C-20°C (14,59,212,214,288,289,591). Whether this change is an intrinsic response of the protein to temperature or whether it is triggered by changes in the microviscosity of the environment remains unresolved.…”
Section: Cholesterol Is Excluded From the Phospholipidmentioning
confidence: 99%